PENGARUH ADVERSITY QUOTIENT, KEMANDIRIAN BELAJAR DAN KECEMASAN TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA MATERI JURNAL PENYESUAIAN - Hidayah, Rizki Nur; Thohiri, Roza; Darma, Jufri; Silalahi, Sondang Aida; Nurhayani, Ulfa (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aims to determine the effect of adversity quotient, learning independence and anxiety on problem-solving ability on the adjustment journal material. This type of research is ex post facto. The population in this study were all students of class X majoring in financial accounting and institutions at SMK Negeri 1 Stabat, totaling 69 students. The sample in this study was 69 students, where the sampling technique was total sampling. Data collection was carried out using research questionnaires and adjustment journal test questions. Then analyze the data with the help of the SPSS 25 application. Based on the regression model formed, it is Y = 21.102 + 0.646X1 + 1.413X2 - 0.258X3 and partial hypothesis testing, there is a significant influence between adversity quotient on problem-solving ability, independence on problem-solving ability and anxiety on problem-solving ability. Furthermore, adversity quotient, learning independence and anxiety simultaneously have a significant effect on problem-solving ability with the magnitude of the influence of the three independent variables being 87.4%, while 12.6% is explained by other relevant variables that were not examined in this study.